2014
DOI: 10.1016/j.jadohealth.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Substance Use Among Perinatally Human Immunodeficiency Virus–Infected and Perinatally Exposed but Uninfected Youth

Abstract: Purpose This study examines risk factors associated with recent substance use (SU) among perinatally HIV-infected (PHIV+) and perinatally exposed, uninfected (PHEU) youth and compares SU lifetime prevalence with the general population of United States (US) adolescents. Methods We conducted cross-sectional and longitudinal analyses of 511 PHIV+ and PHEU youth (mean age at study entry 13.2 years, 51% female, 69% PHIV+, 72% African American) enrolled in a US multi-site prospective cohort study between 2007–2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 34 publications
10
36
2
Order By: Relevance
“…The 0.8% prevalence of APRI > 1.5 in this pediatric cohort appears lower than rates of 3.0–3.9% reported in several studies of HIV-infected adults [79] and much lower than the 8% rate observed in one adult study [10]. This lower prevalence among HIV-infected children is likely attributable to lower rates in HIV-infected children compared to HIV-infected adults of other factors that contribute to liver problems, such as viral hepatitis and alcohol use (only 36% of perinatal HIV AMP participants reported alcohol use [11]). The prevalence of APRI > 1.5 in this US pediatric cohort is also substantially lower than the 3.2% prevalence reported in a large group of children in Latin America [12].…”
Section: Discussionmentioning
confidence: 87%
“…The 0.8% prevalence of APRI > 1.5 in this pediatric cohort appears lower than rates of 3.0–3.9% reported in several studies of HIV-infected adults [79] and much lower than the 8% rate observed in one adult study [10]. This lower prevalence among HIV-infected children is likely attributable to lower rates in HIV-infected children compared to HIV-infected adults of other factors that contribute to liver problems, such as viral hepatitis and alcohol use (only 36% of perinatal HIV AMP participants reported alcohol use [11]). The prevalence of APRI > 1.5 in this US pediatric cohort is also substantially lower than the 3.2% prevalence reported in a large group of children in Latin America [12].…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that some perinatally-infected youth engage in unprotected sex and have multiple partners not all of whom are seroconcordant [40]. Furthermore, substance use, which can potentiate sexual risk behaviors, occurs at levels comparable to the general population as perinatally-infected youth grow older [41]. Many perinatally-infected youth have significant mental health needs [42].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the prevalence and correlates of substance use among PHIV+ youths with studies reporting rates of any or lifetime substance use ranging from 13–60 % [7, 11, 19, 20]. Our current understanding of problematic substance use among PHI-V+ youths is limited because substance use typically begins to take off in middle-older adolescence and PHI-V+ youths are only now reaching this age in large enough numbers to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…perceived peer norms) and contextual (e.g. caregiver psychiatric disorder, substance use in the household) factors appear to confer greater risk [7, 11, 19, 20]. However, these studies were largely cross-sectional and focused on mostly younger adolescence, when rates of problematic substance use and disorder are typically low [22, 23].…”
Section: Introductionmentioning
confidence: 99%